Nutrient Use Efficiency in Wheat (Triticum aestivum L.) Variety, DBW-187, Affected by Different Doses of Nitrogen, Phosphorus and Potassium - Singh, Safal; Das, Nilotpal; Kumar, Atin; Kumar, Rohit; Sachan, Sharad; Singh, Jitendra; Bhattacharya, Sayantika; Shubham (Kurdistan Journal of Applied Research, 2026)
Although nitrogen (N), phosphorus (P), and potassium (K) are important nutrients for the creation of high crop yields that support the growing global population, overuse of these nutrients and their underuse cause ecological damage. Therefore, optimization of NPK use efficiency should be the focus for better sustainable agricultural practices. At Uttaranchal University in Dehradun, Uttarakhand, India, a field experiment named "A comparative study of nutrient use efficiency in wheat (Triticum aestivum L.) variety DBW-187 affected by different doses of NPK" was carried out during the Rabi season (October to March) of 2023–2024. Seven treatments and three replications were used in the randomized complete block design (experiment: T1 was control (no fertilizer), T2 was 25% RDF (recommended dose of fertilizers), T3 was 50% RDF, T4 was 75% RDF, T5 was 100% RDF, T6 was 125% RDF, and T7 was 150% RDF. On December 6, 2023, the DBW-187 cultivar was planted with inorganic fertilizers, specifically urea, DAP (Diammonium Phosphate), and MOP (Muriate of Potash). Seventy five kg ha-1 of nitrogen, 40 kg ha-1 dosages of potassium, and 60 kg ha-1 phosphorus were applied at the base, with the remaining nitrogen being top-dressed at 40 DAS before the second watering. Results showed that application of 100% RDF (150:60:40 kg ha⁻¹ N:P:K) significantly improved crop performance, recording the highest grain yield (75.8 q ha⁻¹), biological yield (189.3 q ha⁻¹), leaf area index (1.97 at 90 DAS), and benefit–cost ratio (2.54) compared with the control. Grain protein content increased with higher fertilizer doses, ranging from 8.24% (control) to 10.75% (150% RDF); however, yields did not increase proportionately beyond 100% RDF. Excess fertilizer application (125–150% RDF) resulted in taller plants and higher protein content but lower nutrient use efficiency and economic returns. Overall, 100% RDF was identified as the optimum fertilizer dose for maximizing yield, nutrient use efficiency, and profitability of wheat variety DBW-187 under irrigated conditions.